Mechanical Properties of Isolated Primary Cilia Measured by Micro-tensile Test and Atomic Force Microscopy - Do, Tien-Dung; Katsuyoshi, Jimuro; Cai, Haonai; Ohashi, Toshiro (Frontiers in Bioengineering and Biotechnology, 2021)
Mechanotransduction is a well-known mechanism by which cells sense their surrounding mechanical environment, convert mechanical stimuli into biochemical signals, and eventually change their morphology and functions. Primary cilia are believed to be mechanosensors existing on the surface of the cell membrane and support cells to sense surrounding mechanical signals. Knowing the mechanical properties of primary cilia is essential to understand their responses, such as sensitivity to mechanical stimuli. Previous studies have so far conducted flow experiments or optical trap techniques to measure the flexural rigidity EI (E: Young’s modulus, I: second moment of inertia) of primary cilia; however, the flexural rigidity is not a material property of materials and depends on mathematical models used in the determination, leading to a discrepancy between studies. For better characterization of primary cilia mechanics, Young’s modulus should be directly and precisely measured. In this study, the tensile Young’s modulus of isolated primary cilia is, for the first time, measured by using an in-house micro-tensile tester. The different strain rates of 0.01–0.3 s−1 were applied to isolated primary cilia, which showed a strain rate–dependent Young’s modulus in the range of 69.5–240.0 kPa on average. Atomic force microscopy was also performed to measure the local Young’s modulus of primary cilia, showing the Young’s modulus within the order of tens to hundreds of kPa. This study could directly provide the global and local Young’s moduli, which will benefit better understanding of primary cilia mechanics.